CONCEPTUAL APPROACHES TO UNDERSTANDING BUSINESS PROCESS RE-ENGINEERING: THEORETICAL BASICS AND PRACTICAL ASPECTS - KOTENOK, Andrii; ZVIERIEV, Bohdan; SOKOLAN, Oleh (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines conceptual approaches to understanding the reengineering of business processes, which is an important tool for increasing the efficiency of enterprises in the conditions of growing competition and rapid changes in the market. The author analyzes the process of reengineering as a key method of optimizing operational processes, focusing on the elimination of inefficient components in production and supply. Reengineering allows you to radically update business structures, which ensures increased productivity and flexibility of enterprises, optimizes interaction between divisions, improves the use of resources and reduces costs. The main focus is on the integration of reengineering with digital technologies, including artificial intelligence and machine learning, which can significantly improve the efficiency of processes. The author emphasizes the importance of taking into account the organizational culture and the human factor for the successful implementation of changes. The article also outlines unexplored aspects that require further scientific analysis, in particular the issue of adapting reengineering to small and medium-sized enterprises, as well as the economic and social consequences of its implementation. Reengineering of business processes allows enterprises to quickly respond to changing market conditions, adapting the business model to new challenges and technologies, which in the long term contributes to increasing the competitiveness and sustainability of enterprises. The author emphasized that reengineering is aimed at innovative restructuring of business organization, which eliminates unnecessary labor costs and creates conditions for productive, creative work of each employee and unit. It is emphasized that reengineering is focused not only on increasing the productivity of each individual business link, but also on optimizing the entire system of interaction, which allows to achieve the maximum effect thanks to joint efforts organized in the most effective way.